HEALTH EDUCATION EFFECT TO WASHING HAND ATTITUDE OF 3-4 GRADE - Herta Candra Nur Anggraeni; Emi Kusumawardani; Dwi Prasetyaningati (STIKES Insan Cendekia Medika Jombang, 2011)
Introduction To the number student of class 3-4 in elementary school Truneng which of opinion that washing hands less important matter hand though clean this is hand very necessary for health. Tendency of students have negative attitude because lack of education given to students and effect of environment that often ignore washing hands. The purpose of this research to know effect of health education to attitude of washing hands to students of class 3-4 in elementary school Truneng district of sub-district Sukomoro of Magetan. In this research uses pra experiment method by one group pretest post test design. Population of this research are all students of class 3-4 in elementary school Truneng a number of 41 students. Sampling technique in this research is Total Sampling namely all population are created to become samples. Variable in this research is health education as independent variable and attitude of washing hands of students as dependent variable. Data management at 7 June-14 June 2014 once health education use instrument in the form of questionnaire. Way analyse data by using editing, coding, scoring, tabulating, and to research statistic test uses Wilcoxon test.Based on research result of 41 respondents before health education done, most of respondents have negative attitude about washing hands that is 29 respondents (70,7%) and after health education done, most of respondents have positive attitude about washing hands a number of 23 respondents (56,1%). Wilcoxon test from variable are obtainable value ρ = 0.001 and α = 0,05 so ρ < α it means H1 accepted.Conclusion of this research says that there is effect of health education to attitude of washing hands to students of class 3-4.